2016
DOI: 10.1101/057059
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A systematic review of post-marital residence patterns in prehistoric hunter-gatherers

Abstract: Background and RationalePost-marital residence patterns refer to where a couple lives after marriage, such as near or with husband's kin (patrilocality) or wife's kin (matrilocality). These patterns influence other aspects of social organization and behavior, and potentially reveal key parts of human nature. Since the 1860s, anthropologists have sought to characterize prehistoric hunter-gatherers' post-marital residence patterns by extrapolating from modern hunter-gatherers' and chimpanzees' behavior. For many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 114 publications
(72 reference statements)
1
5
0
3
Order By: Relevance
“…Although the social organization of the Muisca society is far from completely understood and complex kinship structure characterized the Muisca chiefdoms at different social and political levels, the strong evidence of remarkable reduction of genetic (and morphological) diversity occurring during this period agrees with past hypotheses of strong endogamy among the Muisca society (Broadbent, 1964) and disagree with the results and interpretations of more recent ethnohistoric and genetic studies (Langebaek, 1989;Correa, 2001;. Interestingly, in societies practicing both patrilocal and matrilocal residence, the local provenance of a couple (i.e., both coming from the same community) promotes endogamy (Brewer, 2016). Thus, endogamy is a process likely involved in the important reduction of genetic diversity seen during the final late Holocene although, as mentioned above, more evidence is required to test this hypothesis.…”
Section: Decreasing Genetic Diversity Over Time and Evidence Of Gene Driftsupporting
confidence: 58%
See 2 more Smart Citations
“…Although the social organization of the Muisca society is far from completely understood and complex kinship structure characterized the Muisca chiefdoms at different social and political levels, the strong evidence of remarkable reduction of genetic (and morphological) diversity occurring during this period agrees with past hypotheses of strong endogamy among the Muisca society (Broadbent, 1964) and disagree with the results and interpretations of more recent ethnohistoric and genetic studies (Langebaek, 1989;Correa, 2001;. Interestingly, in societies practicing both patrilocal and matrilocal residence, the local provenance of a couple (i.e., both coming from the same community) promotes endogamy (Brewer, 2016). Thus, endogamy is a process likely involved in the important reduction of genetic diversity seen during the final late Holocene although, as mentioned above, more evidence is required to test this hypothesis.…”
Section: Decreasing Genetic Diversity Over Time and Evidence Of Gene Driftsupporting
confidence: 58%
“…Patrilocality and matrilocality are among the most important residence practices influencing human genetic diversity (Oota et al, 2001;Brewer, 2016;Moravec et al, 2018). In the study region, the patterns of post-marital residence have been less studied for the most part of the Holocene and only for the Muisca period some studies have suggested matrilocality (Langebaek, 1989;Correa, 2001).…”
Section: Alternative Models and Hypothesesmentioning
confidence: 97%
See 1 more Smart Citation
“…Es interesante la comprobación realizada en Asia interior sobre el comportamiento más estructurado del sexo masculino (Y-STRs), cuya diversidad se relaciona con una pauta patrilineal y patrilocal comparado con el femenino (HVS1), cuya variación se explica mejor geográficamente (Marchi et al 2016). En los últimos 10.000 años el análisis de una extensa muestra de poblaciones antiguas a nivel mundial determinó una tendencia hacia la residencia matrilocal, sobre la base de la información de mtDNA y de los isótopos del estroncio (87Sr/86Sr), resultado que refleja la misma tendencia en grupos cazadores y recolectores actuales (Brewer 2016).…”
unclassified
“…Sex differences in orientation to kin also may have deep evolutionary roots. Analyses of strontium isotopes and mitochondrial DNA in archaeologic human remains indicate that prehistoric hunter-gatherers were predominantly endogamous (marriage between fellow community members) and exogamous marriages strained toward matrilocality (married couples living in wife's community) (9). Cross-culturally, women's sisters, mothers, daughters, cousins, and aunts are the most likely and valued potential or actual helpers, apart from husbands, in child rearing (10).…”
Section: Introductionmentioning
confidence: 99%